Weight and neuro-psycho-motor development in children discharged from neonatal intensive care unit - de Souza, Cíntia Ginaid [UNESP]; de Abreu, Luiz Carlos [UNESP]; Valenti, Vitor E. [UNESP]; Reis, Alberto O. A. [UNESP]; Gallo, Paulo R. [UNESP]; Fonseca, Fernando L. A.; Radziavicius, Fernanda R. C.; Siqueira, Arnaldo A. F. [UNESP] (My University, 2012)
Background: Low birth weight affects child growth and development, requiring the intensive use of health services. There are conversely proportional associations between prematurity and academic performance around the world. In this study we evaluated factors involved in weight and neuropsychomotor profile in one and two years old discharged from Intensive Care Units (ICU). Methods/Design: We investigated 203 children from the ICU who were followed for 24+4 months. The research was conducted by collecting data from medical records of patients in a Followup program. We investigated the following variables: inadequate weight at one year old; inadequate weight at two years old and a severe neurological disorder at two years old. Results: We observed increase of almost 20% in the proportion of children which weighted between the 10th and 90th percentiles and decrease of around 40% of children below the 15th percentile, from one to two years old. In almost 60% of the cases neuropsychomotor development was normal at 2 years old, less than 15% of children presented abnormal development. Variables that remained influential for clinical outcome at 1 and 2 years old were related to birth weight and gestational age, except for hypoglycemia. Neurological examination was the most influential variable for severe neurological disturbance. Conclusion: Hypoglycemia was considered a new fact to explain inadequate weight. The results, new in Brazil and difficult in terms of comparison, could be used to identify risk factors and for a better approach of newborn discharged from ICUs.
Keywords: Advance care planning; Child; Epidemiology